Force control of hydraulic actuators using additional hydraulic compliance - Ledezma Pérez, Job Angel (Strojniški vestnik, 2018)
This paper presents an approach for improving the performance of hydraulic force control systems by adding hydraulic compliance. Typically, force control systems require a flexible coupling system, such as a spring between the actuator and the load, to achieve a non-oscillatory response. To avoid the use of springs, this study proposes the use of special hoses to add compliance to the system hydraulically. With this approach, a direct connection between the actuator and the load is feasible, simplifying the mechanical assembly and saving physical space in the axial direction. An analytical model is proposed to estimate the appropriate hydraulic stiffness value and to select a commercial hose based on catalogue data. Moreover, a robust controller based on quantitative feedback theory is designed to improve the stability, performance and disturbance rejection of the force control system. The system performance is demonstrated by dynamic simulation and experimental results.
Keywords: dinamično modeliranje; gibka cev z velikim volumskim raztezkom; hidravlična podajnost; hidravlična regulacija sile; high expansion volumetric hose; hydraulic compliance; hydraulic force control; QFT-based control; regulacija QFT; stisljivost fluidov